IMPACT OF THE COVID-19 PANDEMIC ON IPHONE HOUSE MICRO SMALL AND MEDIUM ENTERPRISES (MSMEs) INCOME IN SERANG CITY - Raden Irna Afriani; Khaeruman Khaeruman; Rika Kartika (Yayasan Education and Social Center, 2022)
The presence of MSMEs has an essential factor in people's lives in the realization of distribution to the community. In addition, MSMEs are a vital point for national economic development. When considering job performance, MSMEs can absorb labor, reducing unemployment and participation to help the government fight unemployment. This research uses qualitative research with a case study approach. Data Collection Methods This research was conducted by observing, interviewing, documenting, and drawing conclusions. The results of this study indicate that the existence of the Covid-19 Pandemic impacts MSMEs, especially iPhone homes. When the current impact includes: (1) iPhone home MSME income before the Covid-19 Pandemic was very stable and normal and even often increased, but due to the presence of traders, the Covid-19 Pandemic has decreased spectacularly to reach 50% or more, (2) Factors-factors that led to a decrease in the income of traders during the Covid-19 pandemic period, the desire to visit the public has decreased. Business people have several attempts to increase their income during this Pandemic by learning technology, providing exemplary service, practicing cleanliness by always complying with health protocols, and offering customer promotions and discounts